2015
DOI: 10.1136/acupmed-2014-010634
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Nitric Oxide and Prostaglandins to the Local Increase in Muscle Blood Flow following Manual Acupuncture in Rats

Abstract: Objective To investigate the contributions of nitric oxide (NO) and prostaglandins (PGs) to the increase in local muscle blood flow (MBF) observed following manual acupuncture (MA). Methods Male Sprague-Dawley rats (n=112; 250-310 g) were injected intraperitoneally with a non-selective NO synthase inhibitor (NG-nitro-Larginine methyl ester hydrochloride: L-NAME; 10, 50 or 500 mg/kg), a non-selective cyclooxygenase inhibitor (indomethacin; 10, 50 or 500 mg/kg), a combination of L-NAME and indomethacin (500 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Interestingly, studies from the acupuncture literature report an initial increase of CGRP and SP after needling in the absence of a LTR (Butts et al, 2016;Wu et al, 2015). The added CGRP may initiate a cascade of vasodilators, to include nitric oxide, which may lead to a washout effect (Shinbara et al, 2013(Shinbara et al, , 2015. Alternatively, the CGRP and SP may work to provide negative feedback onto autoreceptors, ultimately decreasing the release of CGRP and SP (Zhang et al, 2012).…”
Section: Pathophysiology Of the Localized Twitch Responsementioning
confidence: 99%
“…Interestingly, studies from the acupuncture literature report an initial increase of CGRP and SP after needling in the absence of a LTR (Butts et al, 2016;Wu et al, 2015). The added CGRP may initiate a cascade of vasodilators, to include nitric oxide, which may lead to a washout effect (Shinbara et al, 2013(Shinbara et al, , 2015. Alternatively, the CGRP and SP may work to provide negative feedback onto autoreceptors, ultimately decreasing the release of CGRP and SP (Zhang et al, 2012).…”
Section: Pathophysiology Of the Localized Twitch Responsementioning
confidence: 99%
“…Therefore, if a patient has less pain, this could result in an increase in function and activities of daily living. improvements noted in the acupuncture group, may be related to the local increase in blood flow and oxygenation, through pro-inflammatory effects and the mechanism of axon reflexes and the inhibition of the sympathetic nervous system [37,38]. The stimulation of A-Delta and C-afferent fibres would release vasoactive and pro-inflammatory neuropeptides such as calcitonin gene-related peptide (CGRP), substance P, neurokinin and opioids.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, early studies have shown that acupuncture increases MBF in humans [25,26,27] and animals [28,29,30]. Some researchers suggested that it the elevated MBF is caused by increases in nitric oxide and prostaglandins after acupuncture [31]. Notably, circulation improvement is beneficial for muscle growth and the mitigation of atrophy through enhancement of oxygen content in muscle tissue.…”
Section: Discussionmentioning
confidence: 99%